Effectiveness and safety of flexible therapeutic schemes including first- and secondgeneration basal insulins during a pediatric summer diabetes camp - Stefano Tumini; Laura Comegna; Elisabetta Fioretti; Paola Guidone; Gabriella Levantini; Daniele Panichi; Milena Catenaro; Ilaria Rossi; Flavia Amaro; Giusi Graziano; Maria Chiara Rossi; Paola Cipriano (MDPI AG, 2020)
Outcomes of insulin analogues in pediatric diabetes camps are poorly investigated; no data is available about insulin degludec (IDeg).Our aim was to assess impact of insulin therapy adopted by the participants to a 4-day diabetes camp held in 2017, hypothesizing a possible excess risk of hypoglycemia in patients treated with IDeg. Overall, 40 children with type 1 diabetes (mean age 13.4±3.0 years; 62.5% males) attended the camp (20.0% on continuous subcutaneous insulin infusion and 80.0% on multiple daily injections - MDI). Among children in MDI regimen, 71.9% were treated with IDeg as basal insulin and 28.1% with glargine U100 (IGlar). All patients used Lispro or Aspart as short-acting insulin. Daily plan of the camp included educational sessions, physical exercise, 3 main meals and 2 snacks. At the arrival, IGlar and short-acting insulin doses were revised according to existing guidelines, while IDeg dose was revised based on an empirical individualized approach. At the arrival, insulin doses were reduced in 22 participants (-19.4±10.5%), while doses were increased in 17 children (+17.8±12.7%), based on individual needs. No statistically significant between-group difference emerged in mean blood glucose and glucose variability. No excess risk of hypoglycemia was found in the IDeg group. The study suggests similar effectiveness and safety of different insulin schemes when associated with appropriate diabetes education and management, and flexible dose adjustments. Despite its longer halflife and the lack of a validated algorithm, IDeg was not associated with an excess risk of hypoglycemia.